Effect of Acrycoat S100 Concentrations on the Entrapment Efficiency of Domperidone in Microsphere - Maulana, Uli (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Domperidone is an antiemetic that is greatly absorbed in the upper part of the gastrointestinal tract in acidic pH and significantly reduced in alkaline pH. Bioavailability of domperidone is 13–17%. One of an effort in increasing the bioavailability of domperidone is to make a microsphere system that was resistance in the upper part of the gastrointestinal tract. Acrycoat S100 is a polymer that can be used for making a microsphere system and for extended release of the drug. Materials and Methods: This study aims to determine the effect of Acrycoat S100 concentration on entrapment efficiency of domperidone in microsphere which is formulated in four formulas that are F1 50 mg, F2 100 mg, F3 150 mg, and F4 200 mg, containing domperidone and Acrycoat S100 as the materials. The method of making microsphere was solvent evaporation. The entrapment efficiency of domperidone in microsphere was determined using ultraviolet spectroscopic method, and entrapment effiency data were statistically analyzed using SPSS One-way analysis of variance (ANOVA) program. The characterization of domperidone microspheres was organoleptic, particle size measurement and morphology observation using Scanning Electron Microscope (SEM). Results: The result of the determination of entrapment efficiency showed that increasing the concentration of Acrycoat S100 is directly proportional to increasing the entrapment efficiency of domperidone in microsphere and F3 formula has an optimum entrapment efficiency by 78.723% ± 4.259 from the statistical analysis with SPSS One-way ANOVA. Domperidone microsphere was a physically white powder with a distinctive odor. The particle size of microsphere domperidone was 31.88–319.87 μm. The morphology of domperidone microsphere observed with SEM was spheric with rough surface, and the size was 172.9 μm. Discussion: Optimum entrapment efficiency of domperidone in microsphere that was formulated with Acrycoat S100 was 78.723% ± 4.259 and increasing with the increasing of the Acrycoat S100 as its polymer with solvent evaporation method. It might be more with high concentrations of Acrycoat S100. Conclusion: The concentration of Acrycoat S100 was a crucial parameter in entrapment efficiency of domperidone in the microsphere.